Potassium-sodium niobate-based leadless piezoelectric ceramic material as well as preparation method and application thereof

By adding MnO2 to KNN-based piezoelectric ceramics and controlling its content ratio, a stable R-T phase boundary and ferroelectric domain variant was constructed, and the problem of low performance of KNN piezoelectric ceramics was solved, and ultra-high voltage-electric performance and excellent mechanical properties were achieved, which was suitable for the new generation of electronic information devices.

CN119569450AActive Publication Date: 2025-03-07CHENGDU UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411764152.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

During the preparation process, KNN piezoelectric ceramics face problems such as element volatility and stoichiometric deviation, and their piezoelectric and mechanical properties are low, which limits its application in the field of high-tech consumer electronic devices.

Method used

By adding the oxide sintering aider MnO2 to the KNN-based piezoelectric ceramics and controlling its content ratio, a stable R-T phase boundary and ferroelectric domain variant is constructed to form a microstructure with a high degree of densification, thereby optimizing the piezoelectric and mechanical properties of the material.

Benefits of technology

It realizes the ultra-high voltage and excellent mechanical properties of KNN-based lead-free piezoelectric ceramics. The performance indicators are far beyond those of pure KNN piezoelectric ceramics and other KNN piezoelectric ceramics. They are suitable for the new generation of micro, lightweight, and high-sensitivity electronic information devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569450A_ABST
    Figure CN119569450A_ABST
Patent Text Reader

Abstract

The invention discloses a potassium-sodium niobate-based leadless piezoelectric ceramic material and a preparation method and application thereof, and relates to the technical field of functional materials, the chemical formula of the potassium-sodium niobate-based leadless piezoelectric ceramic material is 0.964 K < 0.5 > Na < 0.5 > Nb < 0.955 > Sb < 0.045 > O < 3 >-0.03 Bi < 0.5 > Na < 0.5 > ZrO < 3 >-0.006 Bi < FeO < 3 >-x > MnO < 2 >, x = 0.005-0.04, and x represents a mole fraction. The microstructure, compactness, domain structure, phase boundary, loss and defect concentration of a ternary system KNN-based piezoelectric ceramic material system are regulated and controlled through the intervention of an oxide sintering aid MnO2, so that the brand new KNN-based leadless piezoelectric ceramic with ultrahigh piezoelectric property and excellent mechanical property is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and in particular to a potassium sodium niobate-based lead-free piezoelectric ceramic material and a preparation method and application thereof. Background Art

[0002] Piezoelectric ceramics are an important functional material that can realize the mutual conversion between mechanical energy and electrical energy. Due to its simple preparation process, low cost, excellent performance and strong controllability, it has been widely used in many consumer electronic devices, such as piezoelectric / ferroelectric sensors, drivers, transducers, etc. Lead-based piezoelectric ceramics (such as PZT piezoelectric ceramics) have excellent electrical properties and good temperature stability. They are considered to be the most representative materials in the field of piezoelectric ceramics. They have long dominated the field of consumer electronic devices and served in industries such as civil engineering, electronic equipment, aerospace, and petrochemicals. However, the highly toxic lead element makes lead-based piezoelectric ceramics cause serious harm to human health and the earth's environment during preparation, use, and waste material treatment. With the improvement of people's awareness of their own health and environmental protection, vigorously developing lead-free piezoelectric ceramic materials such as potassium sodium niobate (KNN), barium titanate (BT), bismuth ferrite (BF), and bismuth titanate (BIT) has become a new trend to replace traditional lead-based piezoelectric ceramic materials. Among these lead-free piezoelectric ceramics, KNN piezoelectric ceramics have a higher Curie temperature (T c =410℃), good electrical properties (d 33 =80-120pC / N) and lower sintering temperature. However, compared with commercial lead-based PZT piezoelectric ceramics (d 33 ≥410pC / N), the piezoelectric properties of pure KNN piezoelectric ceramics are still relatively low, which greatly limits their application in the field of high-tech consumer electronic devices. Therefore, in order to promote the development of lead-free and environmentally friendly piezoelectric / ferroelectric devices, it is particularly important to optimize and improve the piezoelectric properties of KNN piezoelectric ceramics.

[0003] At present, there are many strategies to regulate and optimize the electrical properties of KNN piezoelectric ceramics, such as doping, phase boundary engineering, domain engineering, texturing, rapid sintering, etc. Among them, the doping strategy is the most effective and widely used method to achieve the performance optimization of KNN piezoelectric ceramics. Doping can change the phase structure of KNN piezoelectric ceramics and regulate the microstructure and domain structure, thereby achieving the purpose of optimizing electrical properties.

[0004] Although great achievements have been made in the research based on KNN piezoelectric ceramics, KNN piezoelectric ceramics usually face problems such as element volatilization and stoichiometric deviation during the preparation process. Further improving its piezoelectric performance still faces challenges, and the mechanical properties that measure its service reliability and stability are rarely reported. In practical applications, in addition to piezoelectric properties, we also need to consider the mechanical properties of piezoelectric ceramics, such as hardness and fracture toughness. Because piezoelectric ceramics are brittle materials, they are easily affected by external mechanical loads and lead to failure, which seriously limits their service reliability and output stability in practical applications. With the increasing progress of today's human society, piezoelectric information devices will develop towards miniature, light, high sensitivity, high precision, high reliability and high stability, which requires lead-free KNN piezoelectric ceramics to have higher piezoelectric and mechanical properties at the same time. Therefore, the development of a new generation of KNN-based lead-free piezoelectric ceramic materials that have both high piezoelectric and mechanical properties has become a necessary task for the advancement of information and the development of the new era. Summary of the invention

[0005] Based on the problem that the high piezoelectric properties and mechanical properties of the current KNN-based lead-free piezoelectric ceramic materials are still relatively low, the purpose of the present invention is to provide a potassium sodium niobate-based lead-free piezoelectric ceramic material and a preparation method and application thereof. The potassium sodium niobate-based lead-free piezoelectric ceramic material has both ultra-high piezoelectric properties and excellent mechanical properties, and is expected to replace traditional lead-containing piezoelectric ceramic materials and be applied to a new generation of miniature, lightweight, highly sensitive, highly precise, highly reliable and highly stable electronic information devices, making an important contribution to the development of information technology and social era in the new era.

[0006] The present invention is achieved through the following technical solutions:

[0007] In the first aspect, the present application provides a potassium sodium niobate-based lead-free piezoelectric ceramic material, the chemical formula of the potassium sodium niobate-based lead-free piezoelectric ceramic material is 0.964K 0.5 Na 0.5 Nb 0.955 Sb 0.045 O3-0.03Bi 0.5 Na 0.5 ZrO3-0.006BiFeO3-xMnO2, wherein x = 0.005 to 0.04. Specifically, x can be 0.005 or 0.01 or 0.02 or 0.03 or 0.04, and x represents the molar fraction.

[0008] The present invention regulates the microstructure, compactness, domain structure, phase boundary, loss and defect concentration of the ternary KNN-based piezoelectric ceramic material system by introducing the oxide sintering aid MnO2, thereby obtaining a new potassium sodium niobate (KNN)-based lead-free piezoelectric ceramic with both ultra-high piezoelectric performance and excellent mechanical properties. In the present invention, when the MnO2 content is 0.01, the KNN-based piezoelectric ceramic obtains the best comprehensive performance, that is, ultra-high piezoelectric performance d 33 =520pC / N, excellent inverse piezoelectric coefficient d 33 * =505pm / V and higher mechanical hardness H V =4.2GPa and fracture toughness K IC =1.22MPa·m 1 / 2 ; When the MnO2 content is 0.005, the KNN-based piezoelectric ceramics obtain higher piezoelectric properties. 33 =430pC / N and excellent fracture toughness K IC =1.34MPa·m 1 / 2 When the MnO2 content is 0.04, the KNN-based piezoelectric ceramics obtain an ultra-high mechanical hardness H v =6.31GPa. These performance indicators far exceed the electrical and mechanical properties of pure KNN piezoelectric ceramics, and are also better than other KNN piezoelectric ceramic materials reported so far. The KNN-based lead-free piezoelectric ceramic material in the present invention is expected to replace the traditional lead-containing piezoelectric ceramic material and be applied to a new generation of miniature, lightweight, highly sensitive, highly precise, highly reliable and highly stable electronic information devices, making an important contribution to the development of information technology and social era in the new era.

[0009] In a second aspect, the present application provides a method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic material, comprising the following steps:

[0010] (1) According to the chemical formula of the potassium sodium niobate-based lead-free piezoelectric ceramic material, weigh the chemical reagents Na2CO3, K2CO3, Nb2O5, Sb2O3, Bi2O3, ZrO2, Fe2O3 and MnO2 to prepare powder;

[0011] (2) using the powder to perform granulation molding to prepare a disc body;

[0012] (3) performing a debinding process on the disc blank;

[0013] (4) sintering the debinding disc green body to obtain a disc ceramic material;

[0014] (5) The sintered disc ceramic material is subjected to silver plating and polarization treatment to obtain a lead-free piezoelectric ceramic material.

[0015] Furthermore, when preparing the powder in step (1), the weighed chemical reagents are firstly subjected to ball milling treatment, then subjected to drying treatment, and finally subjected to pre-calcination treatment.

[0016] Furthermore, the temperature during the pre-firing treatment is controlled at 820° C. to 880° C., and the temperature is kept at 240 min to 360 min.

[0017] Furthermore, when preparing the disc blank in step (2), the powder material and the polyvinyl alcohol binder are first mixed and dried, and then the dried powder particles are placed in a molding mold and molded on a powder dry pressing molding machine, wherein the molding pressure is 5MPa to 15MPa.

[0018] Furthermore, the prepared disc blank has a diameter of 10 mm and a height of 0.8 mm to 1.5 mm.

[0019] Furthermore, the formed disc blank contains a large amount of PVA binder, which has a great influence on the sintering of the disc green body into porcelain. Therefore, before the green body is sintered, the PVA binder needs to be discharged. First, the formed disc blank is placed on a corundum plate and placed in a muffle furnace for debinding. The debinding process in step (3) includes the following four stages:

[0020] The first stage is to raise the temperature from room temperature to 120°C and keep it for 60 min;

[0021] The second stage is to increase the temperature from 120°C to 500°C and keep it for 180 min;

[0022] The third stage is to increase the temperature from 500°C to 550°C;

[0023] The fourth stage is to increase the temperature from 550°C to 850°C and keep it at that temperature for 120 min, and then cool it naturally to room temperature.

[0024] Furthermore, the debinding disc blank is placed in a muffle furnace for sintering to make it magnetic and improve the material density and mechanical strength. In step (4), the sintering process is carried out by a buried sintering method, the sintering temperature is 1040°C to 1100°C, and the temperature is kept for 240min to 180min. The buried sintering method can reduce the volatilization of elements during the sintering process, that is, the disc blank is covered with corresponding powder.

[0025] Furthermore, the disc ceramic material obtained after sintering does not have piezoelectric functionality. In order to facilitate subsequent device applications, it needs to be electrically polarized. Before polarization, silver paste needs to be applied to the surface of the product to form an electrode.

[0026] The silver-plated polarization treatment method in step (5) is as follows: first, silver paste is evenly applied on both sides of the ceramic to form a continuous silver paste film; then, the ceramic sheet coated with the silver paste is heated to a temperature of 600° C. and kept warm for 20 to 60 minutes to ensure that the silver paste is tightly bonded to the ceramic surface and provides good electrical conductivity; finally, the ceramic disc with electrodes is placed in a polarization device for polarization treatment at a polarization voltage of 2.5 kV to 3.5 kV and the pressure is maintained for 10 to 30 minutes to obtain a lead-free piezoelectric ceramic material, which meets performance testing and engineering requirements.

[0027] In the third aspect, the present application provides an application of a potassium sodium niobate-based lead-free piezoelectric ceramic material, which is prepared by the above-mentioned method, including a new generation of miniature, lightweight, highly sensitive, highly precise, highly reliable and highly stable electronic information devices, such as piezoelectric / ferroelectric sensors or drivers or transducers.

[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0029] (1) The potassium sodium niobate-based lead-free piezoelectric ceramic material of the present invention forms a unique microstructural feature: Sb, Bi and Mg are added to the pure KNN lead-free piezoelectric ceramic according to a certain formula ratio. 0.5 Na 0.5 After ZrO3, BiFeO3 and MnO2, a stable RT phase boundary can be successfully constructed with more ferroelectric domain variants and flat free energy, while forming a highly densified double-peak microstructure, fine strip-shaped domain structure and defect dipoles, which are beneficial to ferroelectric polarization and resistance to mechanical plastic deformation and crack propagation, providing a good ion doping strategy for the development of new lead-free piezoelectric ceramic materials with both high voltage and high mechanical properties.

[0030] (2) The potassium sodium niobate-based lead-free piezoelectric ceramic material of the present invention has good ferroelectric dielectric properties: by adjusting the content ratio of the oxide sintering aid MnO2, when the MnO2 content is 0.01, the KNN-based piezoelectric ceramic obtains the maximum maximum polarization intensity P max =24.7μC / cm 2 With the remnant polarization P r =19.1μC / cm 2 and the lowest coercive field E c =6.3kV / cm, and has the highest bipolar ferroelectric strain S pol =0.204%. In addition, the highest dielectric constant of 3296 and the lowest dielectric loss of 0.026 were also obtained. These findings are conducive to optimizing the piezoelectric activity of the material, thereby obtaining a KNN-based piezoelectric ceramic material with excellent piezoelectric properties.

[0031] (3) The potassium sodium niobate-based lead-free piezoelectric ceramic material of the present invention has excellent piezoelectric properties: by adjusting the content ratio of the oxide sintering aid MnO2, when the MnO2 content is 0.01, the KNN-based piezoelectric ceramic has an ultra-high piezoelectric performance. 33 =520pC / N and excellent inverse piezoelectric coefficient d 33 * =505pm / V. These performance indicators far exceed the electrical properties of pure KNN piezoelectric ceramics and are also better than many commercial lead-containing PZT piezoelectric ceramics. This new KNN-based lead-free piezoelectric ceramic material is expected to replace traditional lead-containing piezoelectric ceramic materials and be used in a new generation of miniature, lightweight, highly sensitive and high-precision electronic information devices.

[0032] (4) The potassium sodium niobate-based lead-free piezoelectric ceramic material of the present invention has obtained ultra-high mechanical properties: by adjusting the content ratio of the oxide sintering aid MnO2, when the MnO2 content is 0.005, the KNN-based piezoelectric ceramic has obtained an ultra-high fracture toughness K IC =1.34MPa·m 1 / 2 When the MnO2 content is 0.04, the KNN-based piezoelectric ceramics obtain an ultra-high mechanical hardness H v =6.31GPa. When the MnO2 content is 0.01, the KNN-based piezoelectric ceramics also obtain excellent mechanical hardness H v =4.2GPa and fracture toughness K IC =1.22MPa·m 1 / 2 . These performance indicators far exceed the mechanical properties of pure KNN piezoelectric ceramics, and are also better than other KNN piezoelectric ceramic materials reported so far. Excellent mechanical behavior enables the ceramic material to maintain its structural integrity and stability when disturbed by external forces, thereby effectively resisting the influence of various working environments. Combined with its excellent piezoelectric properties, this new KNN-based lead-free piezoelectric ceramic material (especially when the MnO2 content is 0.01) is expected to replace traditional lead-containing piezoelectric ceramic materials and be used in a new generation of miniature, lightweight, highly sensitive, highly precise, highly reliable and highly stable electronic information devices, making important contributions to the development of information technology and social era in the new era. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0034] Figure 1 The technical roadmap and performance comparison diagram of the KNNS-BNZ-BF-xMn lead-free piezoelectric ceramics in the embodiments of the present invention; wherein (a) is the technical roadmap of the KNNS-BNZ-BF-xMn lead-free piezoelectric ceramics; (b) is the domain structure morphology of the KNNS-BNZ-BF-xMn lead-free piezoelectric ceramic system, and the fine strip-shaped electric domains and abundant domain walls optimize the electrical and mechanical properties of the material; (c) and (d) are the electrical and mechanical properties of the KNNS-BNZ-BF-xMn lead-free piezoelectric ceramic material in the present invention compared with the performance of other KNN-based piezoelectric ceramics and commercial lead-based PZT ceramics reported so far;

[0035] Figure 2 The crystal structure and microstructure diagram of the KNNS-BNZ-BF-xMn lead-free piezoelectric ceramic in the embodiment of the present invention; wherein (a) is the XRD spectrum of the KNNS-BNZ-BF-xMn lead-free piezoelectric ceramic; (b) is a high-power transmission electron microscope image of the KNNS-BNZ-BF-0.01Mn ceramic under the

[001] crystal axis; (c) is a SEM microstructure diagram of the KNNS-BNZ-BF-0.01Mn ceramic; (d) is a PFM phase diagram of the KNNS-BNZ-BF-0.01Mn ceramic;

[0036] Figure 3 The dielectric behavior and phase diagram of the KNNS-BNZ-BF-xMn lead-free piezoelectric ceramics in the embodiment of the present invention, wherein (a) and (b) are the dielectric-temperature curves of the KNNS-BNZ-BF-xMn lead-free piezoelectric ceramics at low temperature and high temperature, respectively; (c) is the phase diagram of the KNNS-BNZ-BF-xMn ceramics;

[0037] Figure 4 : is a graph of the ferroelectric performance of the KNNS-BNZ-BF-xMn lead-free piezoelectric ceramics in the embodiment of the present invention; wherein (a) is the ferroelectric hysteresis curve of the KNNS-BNZ-BF-xMn ceramics; (b) is the maximum polarization intensity (P max ), residual polarization intensity (P r ) and the coercive field (E c ); (c) is the ferroelectric butterfly curve of KNNS-BNZ-BF-xMn ceramics; (d) is the positive strain (S pos ), negative strain (S neg ) and the total strain (S pol ); (e) is the unipolar strain curve of KNNS-BNZ-BF-xMn ceramics; (f) is the unipolar strain (S uni ) and the inverse piezoelectric coefficient (d33 * );

[0038] Figure 5 Graph showing the dielectric properties and piezoelectric properties of the lead-free piezoelectric ceramics of KNNS-BNZ-BF-xMn in the embodiment of the present invention; wherein (a) is the dielectric constant (ε r ) and dielectric loss (tanθ); (b) is the piezoelectric constant (d 33 ) and electromechanical coupling coefficient (k p );

[0039] Figure 6 Graph showing the results of mechanical plastic deformation test of the lead-free piezoelectric ceramics of KNNS-BNZ-BF-xMn in the present invention; wherein (a, b, c, d, e) are load-displacement curves of the lead-free piezoelectric ceramics of KNNS-BNZ-BF-xMn under nanoindentation; (f) is the indentation depth of the lead-free piezoelectric ceramics of KNNS-BNZ-BF-xMn;

[0040] Figure 7 Graphs showing the hardness and fracture toughness test results of the KNNS-BNZ-BF-xMn lead-free piezoelectric ceramics in the implementation of the present invention; wherein (a, c) are SEM images of the Vickers indentation morphology of the unpolarized and polarized KNNS-BNZ-BF-0.02Mn lead-free piezoelectric ceramics, respectively; and (b, d) are the hardness and fracture toughness of the unpolarized and polarized KNNS-BNZ-BF-xMn lead-free piezoelectric ceramics, respectively. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0042] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] The present invention successfully synthesized the ternary system KNNS-BNZ-BF-xMn lead-free piezoelectric ceramic material through the "chemical doping" strategy, and simultaneously obtained excellent electrical properties and ultra-high mechanical properties in the ceramic sample with component x = 0.01 ( Figure 1), by adding Sb and Bi in a certain ratio to pure KNN lead-free piezoelectric ceramics 0.5 Na 0.5 After ZrO3 and BiFeO3, a ternary system KNNS-BNZ-BF lead-free piezoelectric ceramic with high electrical performance potential is formed. Then, the oxide sintering agent MnO2 is added to the ternary system KNN-based lead-free piezoelectric ceramic. By adjusting the content ratio of the sintering agent, a stable RT phase boundary can be successfully constructed with more ferroelectric domain variants and flat free energy. At the same time, a highly densified bimodal microstructure, a fine strip-shaped domain structure and defect dipoles are formed, which are beneficial to ferroelectric polarization and resistance to mechanical plastic deformation and crack propagation. Finally, a new type of lead-free piezoelectric ceramic with both high voltage and high mechanical properties is obtained. Figure 1 As can be seen from Figure (b), the tiny strip-shaped electric domains and abundant domain walls optimize the electrical and mechanical properties of the material. Figure 1 As can be seen from Figures (c) and (d), KNNS-BNZ-BF-xMn lead-free piezoelectric ceramics have both excellent piezoelectric and mechanical properties, and are expected to replace traditional lead-containing piezoelectric ceramic materials and be used in a new generation of miniature, lightweight, highly sensitive, highly precise, highly reliable and highly stable electronic information devices, making important contributions to the development of information technology and society in the new era. The specific implementation cases of KNNS-BNZ-BF-xMn lead-free piezoelectric ceramics under each component are as follows:

[0044] Example 1

[0045] This embodiment provides a method for preparing a KNNS-BNZ-BF-0.005Mn lead-free piezoelectric ceramic material, which is performed according to the following steps:

[0046] S1. Prepare chemical reagents: Na2CO3 (AR 99.8%), K2CO3 (AR 99%), Nb2O5 (AR 99.95%), Sb2O3 (AR 99.99%), Bi2O3 (AR 99.99%), ZrO2 (AR 99%), Fe2O3 (99.99%) and MnO2 (AR99.95%).

[0047] S2, the chemical reagents in step S1 are mixed according to the stoichiometric formula 0.964K 0.5 Na 0.5 Nb 0.955 Sb 0.045 O3-0.03Bi 0.5 Na 0.5 ZrO3-0.006BiFeO3-0.005MnO2

[0048] (KNNS-BNZ-BF-0.005Mn) Weigh and proportion on a high-precision balance, pour the weighed chemical reagents into a polytetrafluoroethylene ball mill, add anhydrous ethanol as a dispersion medium, and perform ball milling for 720 minutes on a planetary ball mill at a speed of 580 r / min to fully mix the chemical reagents.

[0049] S3. Take out the highly mixed KNNS-BNZ-BF-0.005Mn slurry from the ball mill and place it under a baking lamp for drying. Then, pour the dried slurry into an alumina crucible, cover the crucible with a lid, and place it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850°C and kept warm for 360 minutes. Finally, a KNNS-BNZ-BF-0.005Mn solid solution compound with a specific structure is formed through the solid phase reaction process of pre-sintering.

[0050] S4, transfer the pre-sintered KNNS-BNZ-BF-0.005Mn solid solution compound to a mortar, add 7%wt of polyvinyl alcohol (PVA) binder for stirring and granulation. After that, the dried KNNS-BNZ-BF-0.005Mn particles are formed on a powder dry pressing machine. The forming pressure is 10MPa, and finally a KNNS-BNZ-BF-0.005Mn disc blank with a diameter of 10mm and a height of 1mm is obtained.

[0051] S5. Place the formed KNNS-BNZ-BF-0.005Mn disc blank in a muffle furnace for debinding treatment. The debinding temperature setting process includes: first, the temperature of the muffle furnace is increased from room temperature to 120°C and kept warm for 60 minutes; second, the temperature of the muffle furnace is increased from 120°C to 500°C and kept warm for 180 minutes; then, the temperature of the muffle furnace is increased from 500°C to 550°C; finally, the temperature of the muffle furnace is increased from 550°C to 850°C and kept warm for 120 minutes, and then naturally cooled to room temperature. Next, the debinding KNNS-BNZ-BF-0.005Mn disc blank is placed in the muffle furnace again for sintering treatment to make it magnetic and improve the material density and mechanical strength. In the sintering process, the buried burning method is usually used to reduce the volatilization of elements, that is, the disc blank is covered with corresponding powder. The sintering temperature is 1070° C., and the temperature is maintained for 180 min. The sintered product is then naturally cooled to room temperature to obtain a KNNS-BNZ-BF-0.005Mn ceramic disc material.

[0052] S6. Use a brush to dip a small amount of silver paste and evenly apply it on both sides of the sintered KNNS-BNZ-BF-0.005Mn ceramic disc to form a continuous silver paste film. Then place it in a muffle furnace for heating to ensure that the silver paste is tightly bonded to the ceramic surface and forms an electrode. The heating temperature is 600°C and the temperature is kept for 30 minutes. Finally, the KNNS-BNZ-BF-0.005Mn ceramic disc with electrodes is placed in a polarization device for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the KNNS-BNZ-BF-0.005Mn lead-free piezoelectric ceramic material that meets the performance test is obtained.

[0053] The following performance characteristics were performed on the KNNS-BNZ-BF-0.005Mn lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0054] 1) XRD and variable temperature dielectric test were used to test KNNS-BNZ-BF-0.005Mn ceramics, proving the structural characteristics of RT phase coexistence ( Figure 2 and Figure 3 ), and also obtained a higher dielectric constant (ε r =3139) and lower dielectric loss (tanθ=0.029) ( Figure 5 ).

[0055] 2) The hysteresis curve and butterfly curve of KNNS-BNZ-BF-0.005Mn ceramic sample were tested by ferroelectric analyzer, and a larger ferroelectric maximum polarization intensity (P max =24.1μC / cm 2 ), a larger residual polarization intensity (P r =18μC / cm 2 ), smaller coercive field (E c =7.5kV / cm), a large bipolar ferroelectric total strain (S pol =0.179%), and a large unipolar ferroelectric strain (S uni =0.113%) and a larger inverse piezoelectric coefficient (d 33 * =417pm / V)( Figure 4 ).

[0056] 3) Use quasi-static 33 The piezoelectric constant and electromechanical coupling coefficient of KNNS-BNZ-BF-0.005Mn ceramic material were tested by measuring instrument and impedance analyzer, and a larger piezoelectric constant (d 33 =430pC / N) and a higher electromechanical coupling coefficient (k p =0.45)( Figure 5 ).

[0057] 4) The load-displacement curve of KNNS-BNZ-BF-0.005Mn ceramic material was obtained by nanoindentation, and the maximum indentation depth (H m =643nm)( Figure 6 ). In addition, the hardness and fracture toughness of KNNS-BNZ-BF-0.005Mn ceramic material were obtained by using Vickers indenter, where the hardness value is: v =3.6Gpa, polarization H v =3.4GPa; fracture toughness value: unpolarized K IC =1.32MPa·m 1 / 2 , polarization K IC =1.34MPa·m 1 / 2 ( Figure 7 ).

[0058] from Figure 7 It can be seen from Figures (b, d) that when the MnO2 content is 0.005, the KNN-based piezoelectric ceramics obtain an ultra-high fracture toughness K IC =1.34MPa·m 1 / 2 .

[0059] Example 2

[0060] This embodiment provides a method for preparing a KNNS-BNZ-BF-0.01Mn lead-free piezoelectric ceramic material, which is performed according to the following steps:

[0061] S1. Prepare chemical reagents: Na2CO3 (AR 99.8%), K2CO3 (AR 99%), Nb2O5 (AR 99.95%), Sb2O3 (AR 99.99%), Bi2O3 (AR 99.99%), ZrO2 (AR 99%), Fe2O3 (99.99%) and MnO2 (AR99.95%).

[0062] S2. The above experimental materials are mixed according to the chemical stoichiometric formula 0.964K 0.5 Na 0.5 Nb 0.955 Sb 0.045 O3-0.03Bi 0.5 Na 0.5 ZrO3-0.006BiFeO3-0.01MnO2 (KNNS-BNZ-BF-0.01Mn) was weighed and proportioned on a high-precision balance, and the weighed chemical reagents were poured into a polytetrafluoroethylene ball mill jar. Anhydrous ethanol was added as a dispersion medium, and ball milling was performed on a planetary ball mill for 720 minutes at a rotation speed of 580 r / min to fully mix the chemical reagents.

[0063] S3. Take out the highly mixed KNNS-BNZ-BF-0.01Mn slurry from the ball mill and place it under a baking lamp for drying. Then, pour the dried slurry into an alumina crucible, cover the crucible with a lid, and place it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850°C and kept warm for 360 minutes. Finally, a KNNS-BNZ-BF-0.01Mn solid solution compound with a specific structure is formed through the solid phase reaction process of pre-sintering.

[0064] S4, transfer the pre-sintered KNNS-BNZ-BF-0.01Mn solid solution compound to a mortar, add 7%wt polyvinyl alcohol (PVA) binder for stirring and granulation. After that, the dried KNNS-BNZ-BF-0.01Mn particles are formed on a powder dry pressing machine. The forming pressure is 10MPa, and finally a KNNS-BNZ-BF-0.01Mn disc blank with a diameter of 10mm and a height of 1mm is obtained.

[0065] S5. Place the formed KNNS-BNZ-BF-0.01Mn disc blank in a muffle furnace for debinding treatment. The debinding temperature setting process includes: first, the temperature of the muffle furnace is increased from room temperature to 120°C and kept warm for 60 minutes; second, the temperature of the muffle furnace is increased from 120°C to 500°C and kept warm for 180 minutes; then, the temperature of the muffle furnace is increased from 500°C to 550°C; finally, the temperature of the muffle furnace is increased from 550°C to 850°C and kept warm for 120 minutes, and then naturally cooled to room temperature. Next, the debinding KNNS-BNZ-BF-0.01Mn disc blank is placed in the muffle furnace again for sintering treatment to make it magnetic and improve the material density and mechanical strength. In the sintering process, the buried burning method is usually used to reduce the volatilization of elements, that is, the disc blank is covered with corresponding powder. The sintering temperature is 1070° C., and the temperature is maintained for 180 min. The sintered product is then naturally cooled to room temperature to obtain a KNNS-BNZ-BF-0.01Mn ceramic disc material.

[0066] S6. Use a brush to dip a small amount of silver paste and evenly apply it on both sides of the sintered KNNS-BNZ-BF-0.01Mn ceramic disc to form a continuous silver paste film. Then place it in a muffle furnace for heating to ensure that the silver paste is tightly bonded to the ceramic surface and forms an electrode. The heating temperature is 600°C and the temperature is kept for 30 minutes. Finally, the KNNS-BNZ-BF-0.01Mn ceramic disc with electrodes is placed in a polarization device for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the KNNS-BNZ-BF-0.01Mn lead-free piezoelectric ceramic material that meets the performance test is obtained.

[0067] The following performance characterizations were performed on the KNNS-BNZ-BF-0.01Mn lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0068] 1) XRD and variable temperature dielectric test were used to test KNNS-BNZ-BF-0.01Mn ceramics, proving the structural characteristics of RT phase coexistence ( Figure 2 and Figure 3 ). The crystal structure of KNNS-BNZ-BF-0.01Mn ceramics was observed using HRTEM, and the neatly arranged atomic morphology and high-quality crystallinity were found ( Figure 2 ). At the same time, the microstructure was observed by SEM, which showed the characteristics of bimodal grain distribution and excellent density. Moreover, the domain structure of the ceramic was observed by PFM, which revealed a smaller strip domain structure with lower free energy, which helps to improve the piezoelectric performance. Finally, the ceramic obtained the highest dielectric constant (ε r =3296) and the lowest dielectric loss (tanθ=0.026) ( Figure 5 ).

[0069] 2) The hysteresis curve and butterfly curve of KNNS-BNZ-BF-0.01Mn ceramic sample were tested by ferroelectric analyzer, and the maximum ferroelectric maximum polarization intensity (P max =24.7μC / cm 2 ), the maximum residual polarization intensity (P r =19.1μC / cm 2 ), smaller coercive field (E c =6.9kV / cm), the maximum bipolar ferroelectric total strain (S pol =0.205%), the maximum unipolar ferroelectric strain (S uni =0.136%) and the maximum inverse piezoelectric coefficient (d 33 * =505pm / V)( Figure 4 ).

[0070] from Figure 4 As can be seen from Figure (b), when x = 0.01, the ceramic system obtains the best maximum polarization intensity (P max =24.7μC / cm 2 ) and the remanent polarization intensity (P r =19.1μC / cm 2 ), and has a smaller coercive field (E c =6.3kV / cm).

[0071] from Figure 4 As can be seen from Figure (d), when x = 0.01, the ceramic system obtains the best positive strain (Spos =0.137%), negative strain (S pos =0.067%) and the total strain (S pol =0.204%).

[0072] from Figure 4 As can be seen from Figure (f), when x = 0.01, the ceramic system obtains the best unipolar strain (S uni =0.136%) and the inverse piezoelectric coefficient (d 33 * =505pm / V).

[0073] 3) Use quasi-static 33 The piezoelectric constant and electromechanical coupling coefficient of KNNS-BNZ-BF-0.01Mn ceramic material were tested by measuring instrument and impedance analyzer, and the maximum piezoelectric constant (d 33 =520pC / N) and the maximum electromechanical coupling coefficient (k p =0.526)( Figure 5 ).

[0074] from Figure 5 As can be seen from Figure (a), when x = 0.01, the ceramic system obtains the best dielectric constant (ε r =3296) and minimum dielectric loss (tanθ=0.026).

[0075] from Figure 5 As can be seen from Figure (b), when x = 0.01, the ceramic system obtains the best piezoelectric constant (d 33 =520pC / N) and electromechanical coupling coefficient (k p =0.526).

[0076] 4) The load-displacement curve of KNNS-BNZ-BF-0.01Mn ceramic material was obtained by nanoindentation, and the minimum indentation depth (H) of the ceramic was obtained. m =609nm)( Figure 6 ), showing good resistance to plastic deformation. In addition, the hardness and fracture toughness of KNNS-BNZ-BF-0.01Mn ceramic material were obtained by Vickers indentation tester, where the hardness value is: v =4.2Gpa, polarization H v =4.0GPa; fracture toughness value: unpolarized K IC =1.19MPa·m 1 / 2 , polarization K IC =1.22MPa·m 1 / 2 ( Figure 7 ).

[0077] from Figure 7 It can be seen from Figures (b, d) that when the MnO2 content is 0.01, the electrical properties of the KNN-based piezoelectric ceramics are optimal, and at the same time, excellent mechanical hardness H is obtained. v =4.2GPa and fracture toughness K IC =1.22MPa·m 1 / 2 .

[0078] Example 3

[0079] This embodiment provides a method for preparing a KNNS-BNZ-BF-0.02Mn lead-free piezoelectric ceramic material, which is performed according to the following steps:

[0080] S1. Prepare chemical reagents: Na2CO3 (AR 99.8%), K2CO3 (AR 99%), Nb2O5 (AR 99.95%), Sb2O3 (AR 99.99%), Bi2O3 (AR 99.99%), ZrO2 (AR 99%), Fe2O3 (99.99%) and MnO2 (AR99.95%).

[0081] S2. The above experimental materials are mixed according to the chemical stoichiometric formula 0.964K 0.5 Na 0.5 Nb 0.955 Sb 0.045 O3-0.03Bi 0.5 Na 0.5 ZrO3-0.006BiFeO3-0.02MnO2 (KNNS-BNZ-BF-0.02Mn) was weighed and proportioned on a high-precision balance, and the weighed chemical reagents were poured into a polytetrafluoroethylene ball mill jar. Anhydrous ethanol was added as a dispersion medium and ball milled for 720 minutes on a planetary ball mill at a rotation speed of 580 r / min to fully mix the chemical reagents.

[0082] S3. Take out the highly mixed KNNS-BNZ-BF-0.02Mn slurry from the ball mill and place it under a baking lamp for drying. Then, pour the dried slurry into an alumina crucible, cover the crucible with a lid, and place it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850°C and kept warm for 360 minutes. Finally, a KNNS-BNZ-BF-0.02Mn solid solution compound with a specific structure is formed through the solid phase reaction process of pre-sintering.

[0083] S4, transfer the pre-sintered KNNS-BNZ-BF-0.02Mn solid solution compound to a mortar, add 7%wt of polyvinyl alcohol (PVA) binder for stirring and granulation. After that, the dried KNNS-BNZ-BF-0.02Mn particles are formed on a powder dry pressing machine. The forming pressure is 10MPa, and finally a KNNS-BNZ-BF-0.02Mn disc blank with a diameter of 10mm and a height of 1mm is obtained.

[0084] S5. Place the formed KNNS-BNZ-BF-0.02Mn disc blank in a muffle furnace for debinding treatment. The debinding temperature setting process includes: first, the temperature of the muffle furnace is increased from room temperature to 120°C and kept warm for 60 minutes; second, the temperature of the muffle furnace is increased from 120°C to 500°C and kept warm for 180 minutes; then, the temperature of the muffle furnace is increased from 500°C to 550°C; finally, the temperature of the muffle furnace is increased from 550°C to 850°C and kept warm for 120 minutes, and then naturally cooled to room temperature. Next, the debinding KNNS-BNZ-BF-0.02Mn disc blank is placed in the muffle furnace again for sintering treatment to make it magnetic and improve the material density and mechanical strength. In the sintering process, the buried burning method is usually used to reduce the volatilization of elements, that is, the disc blank is covered with corresponding powder. The sintering temperature is 1070° C., and the temperature is maintained for 180 min. The sintered product is then naturally cooled to room temperature to obtain a KNNS-BNZ-BF-0.02Mn ceramic disc material.

[0085] S6. Use a brush to dip a small amount of silver paste and evenly apply it on both sides of the sintered KNNS-BNZ-BF-0.02Mn ceramic disc to form a continuous silver paste film. Then place it in a muffle furnace for heating to ensure that the silver paste is tightly bonded to the ceramic surface and forms an electrode. The heating temperature is 600°C and the temperature is kept for 30 minutes. Finally, the KNNS-BNZ-BF-0.02Mn ceramic disc with electrodes is placed in a polarization device for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the KNNS-BNZ-BF-0.02Mn lead-free piezoelectric ceramic material that meets the performance test is obtained.

[0086] The following performance characteristics were performed on the KNNS-BNZ-BF-0.02Mn lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0087] 1) XRD and variable temperature dielectric test were used to test KNNS-BNZ-BF-0.02Mn ceramics, proving the structural characteristics of RT phase coexistence ( Figure 2 and Figure 3 ). At the same time, a higher dielectric constant (ε r =3001) and lower dielectric loss (tanθ=0.028)( Figure 5 ).

[0088] 2) The hysteresis curve and butterfly curve of KNNS-BNZ-BF-0.02Mn ceramic sample were tested by ferroelectric analyzer, and a larger ferroelectric maximum polarization intensity (P max =20.9μC / cm 2 ), a larger residual polarization intensity (P r =14.7μC / cm 2 ), smaller coercive field (E c =8.1kV / cm), a large bipolar ferroelectric total strain (S pol =0.176%), and a large unipolar ferroelectric strain (S uni =0.135%) and a larger inverse piezoelectric coefficient (d 33 * =500pm / V)( Figure 4 ).

[0089] 3) Use quasi-static 33 The piezoelectric constant and electromechanical coupling coefficient of KNNS-BNZ-BF-0.02Mn ceramic material were tested by measuring instrument and impedance analyzer, and a larger piezoelectric constant (d 33 =409pC / N) and a higher electromechanical coupling coefficient (k p =0.433)( Figure 5 ).

[0090] 4) The load-displacement curve of KNNS-BNZ-BF-0.02Mn ceramic material was obtained by nanoindentation, and the minimum indentation depth (H) of the ceramic was obtained. m =594nm)( Figure 6 ). In addition, the indentation and crack extension morphology, hardness and fracture toughness of KNNS-BNZ-BF-0.02Mn ceramic material were obtained by Vickers indentation instrument, where the hardness value is: v =4.5Gpa, polarization H v =4.35GPa; fracture toughness value: unpolarized K IC =1.213MPa·m 1 / 2 , polarization K IC =1.245MPa·m 1 / 2 ( Figure 7 ).

[0091] Example 4

[0092] This embodiment provides a method for preparing a KNNS-BNZ-BF-0.03Mn lead-free piezoelectric ceramic material, which is performed according to the following steps:

[0093] S1. Prepare chemical reagents: Na2CO3 (AR 99.8%), K2CO3 (AR 99%), Nb2O5 (AR 99.95%), Sb2O3 (AR 99.99%), Bi2O3 (AR 99.99%), ZrO2 (AR 99%), Fe2O3 (99.99%) and MnO2 (AR99.95%).

[0094] S2. The above experimental materials are mixed according to the chemical stoichiometric formula 0.964K 0.5 Na 0.5 Nb 0.955 Sb 0.045 O3-0.03Bi 0.5 Na 0.5 ZrO3-0.006BiFeO3-0.03MnO2 (KNNS-BNZ-BF-0.03Mn) was weighed and proportioned on a high-precision balance, and the weighed chemical reagents were poured into a polytetrafluoroethylene ball mill jar. Anhydrous ethanol was added as a dispersion medium, and ball milling was performed on a planetary ball mill for 720 minutes at a rotation speed of 580 r / min to fully mix the chemical reagents.

[0095] S3. Take out the highly mixed KNNS-BNZ-BF-0.03Mn slurry from the ball mill and place it under a baking lamp for drying. Then, pour the dried slurry into an alumina crucible, cover the crucible with a lid, and place it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850°C and kept warm for 360 minutes. Finally, a KNNS-BNZ-BF-0.03Mn solid solution compound with a specific structure is formed through the solid phase reaction process of pre-sintering.

[0096] S4, transfer the pre-sintered KNNS-BNZ-BF-0.03Mn solid solution compound to a mortar, add 7%wt of polyvinyl alcohol (PVA) binder for stirring and granulation. After that, the dried KNNS-BNZ-BF-0.03Mn particles are formed on a powder dry pressing machine. The forming pressure is 10MPa, and finally a KNNS-BNZ-BF-0.03Mn disc blank with a diameter of 10mm and a height of 1mm is obtained.

[0097] S5. Place the formed KNNS-BNZ-BF-0.03Mn disc blank in a muffle furnace for debinding treatment. The debinding temperature setting process includes: first, the temperature of the muffle furnace is increased from room temperature to 120°C and kept warm for 60 minutes; second, the temperature of the muffle furnace is increased from 120°C to 500°C and kept warm for 180 minutes; then, the temperature of the muffle furnace is increased from 500°C to 550°C; finally, the temperature of the muffle furnace is increased from 550°C to 850°C and kept warm for 120 minutes, and then naturally cooled to room temperature. Next, the debinding KNNS-BNZ-BF-0.03Mn disc blank is placed in the muffle furnace again for sintering treatment to make it magnetic and improve the material density and mechanical strength. In the sintering process, the buried burning method is usually used to reduce the volatilization of elements, that is, the disc blank is covered with corresponding powder. The sintering temperature is 1070° C., and the temperature is maintained for 180 min. The sintered product is then naturally cooled to room temperature to obtain a KNNS-BNZ-BF-0.03Mn ceramic disc material.

[0098] S6. Use a brush to dip a small amount of silver paste and evenly apply it on both sides of the sintered KNNS-BNZ-BF-0.03Mn ceramic disc to form a continuous silver paste film. Then place it in a muffle furnace for heating to ensure that the silver paste is tightly bonded to the ceramic surface and forms an electrode. The heating temperature is 600°C and the temperature is kept for 30 minutes. Finally, the KNNS-BNZ-BF-0.03Mn ceramic disc with electrodes is placed in a polarization device for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the KNNS-BNZ-BF-0.03Mn lead-free piezoelectric ceramic material that meets the performance test is obtained.

[0099] The following performance characteristics were performed on the KNNS-BNZ-BF-0.03Mn lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0100] 1) XRD and variable temperature dielectric test were used to test KNNS-BNZ-BF-0.03Mn ceramics, proving the structural characteristics of RT phase coexistence ( Figure 2 and Figure 3 ). At the same time, a higher dielectric constant (ε r =2898) and lower dielectric loss (tanθ=0.029) ( Figure 5 ).

[0101] 2) The hysteresis curve and butterfly curve of KNNS-BNZ-BF-0.03Mn ceramic sample were tested by ferroelectric analyzer, and a larger ferroelectric maximum polarization intensity (P max =20.2μC / cm 2 ), a larger residual polarization intensity (P r =12μC / cm 2), smaller coercive field (E c =8.15kV / cm), a large bipolar ferroelectric total strain (S pol =0.171%), and a large unipolar ferroelectric strain (S uni =0.128%) and a larger inverse piezoelectric coefficient (d 33 * =474pm / V)( Figure 4 ).

[0102] 3) Use quasi-static 33 The piezoelectric constant and electromechanical coupling coefficient of KNNS-BNZ-BF-0.03Mn ceramic material were tested by measuring instrument and impedance analyzer, and a larger piezoelectric constant (d 33 =371pC / N) and a higher electromechanical coupling coefficient (k p =0.429)( Figure 5 ).

[0103] 4) The load-displacement curve of KNNS-BNZ-BF-0.03Mn ceramic material was obtained by nanoindentation, and the minimum indentation depth (H) of the ceramic was obtained. m =608nm)( Figure 6 ). In addition, the hardness and fracture toughness of KNNS-BNZ-BF-0.03Mn ceramic material were obtained by using Vickers indenter, where the hardness value is: v =4.34Gpa, polarization H v =4.1GPa; fracture toughness value: unpolarized K IC =1.233MPa·m 1 / 2 , polarization K IC =1.254MPa·m 1 / 2 ( Figure 7 ).

[0104] Example 5

[0105] This embodiment provides a method for preparing a KNNS-BNZ-BF-0.04Mn lead-free piezoelectric ceramic material, which is performed according to the following steps:

[0106] S1. Prepare chemical reagents: Na2CO3 (AR 99.8%), K2CO3 (AR 99%), Nb2O5 (AR 99.95%), Sb2O3 (AR 99.99%), Bi2O3 (AR 99.99%), ZrO2 (AR 99%), Fe2O3 (99.99%) and MnO2 (AR99.95%).

[0107] S2. The above experimental materials are mixed according to the chemical stoichiometric formula 0.964K 0.5 Na0.5 Nb 0.955 Sb 0.045 O3-0.03Bi 0.5 Na 0.5 ZrO3-0.006BiFeO3-0.04MnO2 (KNNS-BNZ-BF-0.04Mn) was weighed and proportioned on a high-precision balance, and the weighed chemical reagents were poured into a polytetrafluoroethylene ball mill jar. Anhydrous ethanol was added as a dispersion medium, and the ball milling treatment was carried out on a planetary ball mill for 720 minutes at a rotation speed of 580 r / min to fully mix the chemical reagents.

[0108] S3. Take out the highly mixed KNNS-BNZ-BF-0.04Mn slurry from the ball mill and place it under a baking lamp for drying. Then, pour the dried slurry into an alumina crucible, cover the crucible with a lid, and place it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850°C and kept warm for 360 minutes. Finally, a KNNS-BNZ-BF-0.04Mn solid solution compound with a specific structure is formed through the solid phase reaction process of pre-sintering.

[0109] S4, transfer the pre-sintered KNNS-BNZ-BF-0.04Mn solid solution compound to a mortar, add 7%wt of polyvinyl alcohol (PVA) binder for stirring and granulation. After that, the dried KNNS-BNZ-BF-0.04Mn particles are formed on a powder dry pressing machine. The forming pressure is 10MPa, and finally a KNNS-BNZ-BF-0.04Mn disc blank with a diameter of 10mm and a height of 1mm is obtained.

[0110] S5. Place the formed KNNS-BNZ-BF-0.04Mn disc blank in a muffle furnace for debinding treatment. The debinding temperature setting process includes: first, the temperature of the muffle furnace is increased from room temperature to 120°C and kept warm for 60 minutes; second, the temperature of the muffle furnace is increased from 120°C to 500°C and kept warm for 180 minutes; then, the temperature of the muffle furnace is increased from 500°C to 550°C; finally, the temperature of the muffle furnace is increased from 550°C to 850°C and kept warm for 120 minutes, and then naturally cooled to room temperature. Next, the debinding KNNS-BNZ-BF-0.04Mn disc blank is placed in the muffle furnace again for sintering treatment to make it magnetic and improve the material density and mechanical strength. In the sintering process, the buried burning method is usually used to reduce the volatilization of elements, that is, the disc blank is covered with corresponding powder. The sintering temperature is 1070°C, and the temperature is kept for 180 minutes, followed by natural cooling to room temperature to obtain a KNNS-BNZ-BF-0.04Mn ceramic disc material.

[0111] S6. Use a brush to dip a small amount of silver paste and evenly apply it on both sides of the sintered KNNS-BNZ-BF-0.04Mn ceramic disc to form a continuous silver paste film. Then place it in a muffle furnace for heating to ensure that the silver paste is tightly bonded to the ceramic surface and forms an electrode. The heating temperature is 600°C and the temperature is kept for 30 minutes. Finally, the KNNS-BNZ-BF-0.04Mn ceramic disc with electrodes is placed in a polarization device for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the KNNS-BNZ-BF-0.04Mn lead-free piezoelectric ceramic material that meets the performance test is obtained.

[0112] The following performance characteristics were performed on the KNNS-BNZ-BF-0.04Mn lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0113] 1) XRD and variable temperature dielectric test were used to test KNNS-BNZ-BF-0.04Mn ceramics, proving the pseudo cubic phase structural characteristics ( Figure 2 and Figure 3 ),from Figure 3 It can be seen that the addition of MnO2 has a great influence on the dielectric properties of ceramics. When the doping is low, there is a stable RT phase boundary. When the doping is high, the RT phase boundary disappears and a pseudo cubic phase structure is formed. At the same time, a lower dielectric constant (ε r =2217) and higher dielectric loss (tanθ=0.035) ( Figure 5 ).

[0114] 2) The hysteresis curve and butterfly curve of KNNS-BNZ-BF-0.04Mn ceramic sample were tested by ferroelectric analyzer, and a smaller ferroelectric maximum polarization intensity (P max =13.9μC / cm 2 ), smaller residual polarization intensity (P r =4.01μC / cm 2 ), smaller coercive field (E c =5.9kV / cm), smaller bipolar ferroelectric total strain (S pol =0.065%), and a small unipolar ferroelectric strain (S uni =0.063%) and a larger inverse piezoelectric coefficient (d 33 * =233pm / V)( Figure 4 ).

[0115] 3) Use quasi-static 33 The piezoelectric constant and electromechanical coupling coefficient of KNNS-BNZ-BF-0.04Mn ceramic material were tested by measuring instrument and impedance analyzer, and a smaller piezoelectric constant (d 33=86pC / N) and a smaller electromechanical coupling coefficient (k p =0.16)( Figure 5 ).

[0116] 4) The load-displacement curve of KNNS-BNZ-BF-0.04Mn ceramic material was obtained by nanoindentation, and the minimum indentation depth (H m =566nm)( Figure 6 ), indicating excellent resistance to plastic deformation. In addition, the hardness and fracture toughness of KNNS-BNZ-BF-0.04Mn ceramic material were obtained by Vickers indentation tester, where the hardness value is: v =6.3Gpa, polarization H v =5.7GPa; fracture toughness value: unpolarized K IC =1.101MPa·m 1 / 2 , polarization K IC =1.147MPa·m 1 / 2 ( Figure 7 ).

[0117] from Figure 7 As can be seen from Figures (b, d), when the MnO2 content is 0.04, the KNN-based piezoelectric ceramics obtain an ultra-high mechanical hardness H v =6.31Gpa.

[0118] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A potassium sodium niobate-based lead-free piezoelectric ceramic material, characterized in that: The chemical formula of the potassium sodium niobate-based lead-free piezoelectric ceramic material is 0.964K 0.5 Na 0.5 Nb 0.955 Sb 0.045 O3-0.03Bi 0.5 Na 0.5 ZrO3-0.006BiFeO3-xMnO2, wherein x=0.005~0.04, and x represents the molar fraction.

2. A method for preparing the potassium sodium niobate-based lead-free piezoelectric ceramic material according to claim 1, characterized in that: The following steps are involved: (1) According to the chemical formula of the potassium sodium niobate-based lead-free piezoelectric ceramic material, weigh the chemical reagents Na2CO3, K2CO3, Nb2O5, Sb2O3, Bi2O3, ZrO2, Fe2O3 and MnO2 to prepare powder; (2) using the powder to perform granulation molding to prepare a disc body; (3) performing a debinding process on the disc blank; (4) sintering the debinding disc green body to obtain a disc ceramic material; (5) The sintered disc ceramic material is subjected to silver plating and polarization treatment to obtain a lead-free piezoelectric ceramic material.

3. The method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic material according to claim 2, characterized in that: When preparing the powder in step (1), the weighed chemical reagents are firstly subjected to ball milling treatment, then to drying treatment, and finally to pre-calcination treatment.

4. The method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic material according to claim 3, characterized in that: The temperature during the pre-firing treatment is controlled at 820°C to 880°C, and the temperature is kept for 240min to 360min.

5. The method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic material according to claim 2, characterized in that: When preparing the disc blank in step (2), the powder and the polyvinyl alcohol binder are first stirred and mixed and then dried. The dried powder particles are then placed in a molding mold and molded on a powder dry pressing machine.

6. The method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic material according to claim 5, characterized in that: The prepared disc blank has a diameter of 10 mm and a height of 0.8 mm to 1.5 mm.

7. The method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic material according to claim 2, characterized in that: The debinding process in step (3) includes the following four stages: The first stage is to raise the temperature from room temperature to 120°C and keep it for 60 min; The second stage is to increase the temperature from 120°C to 500°C and keep it for 180 min; The third stage is to increase the temperature from 500°C to 550°C; The fourth stage is to increase the temperature from 550°C to 850°C and keep it at that temperature for 120 min, and then cool it naturally to room temperature.

8. The method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic material according to claim 2, characterized in that: In step (4), the sintering treatment is carried out by the buried firing method, the sintering temperature is 1040° C. to 1100° C., and the heat preservation time is 180 min to 240 min.

9. The method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic material according to claim 2, characterized in that: The silver-plated polarization treatment method in step (5) is as follows: first, silver paste is evenly applied on both sides of the ceramic to form a continuous silver paste film; then, the ceramic sheet coated with silver paste is heated to ensure that the silver paste is tightly bonded to the ceramic surface and provides good conductive properties; finally, the ceramic disc with electrodes is placed in a polarization device for polarization treatment to obtain a lead-free piezoelectric ceramic material.

10. An application of the potassium sodium niobate-based lead-free piezoelectric ceramic material according to claim 1 or the potassium sodium niobate-based lead-free piezoelectric ceramic material prepared by the preparation method according to any one of claims 2 to 9, characterized in that: Includes piezoelectric / ferroelectric sensors or actuators or transducers.

Citation Information

Patent Citations

  • Leadless piezoelectric ceramic and preparation method thereof

    CN107382316A

  • Anti-reduction potassium sodium niobate-based leadless piezoelectric ceramic and preparation method thereof

    CN108623303A

  • Potassium-sodium niobate-based leadless piezoelectric ceramic and preparation method thereof

    CN111302797A

  • Potassium-sodium niobate-based lead-free piezoelectric ceramic material with ultralow dielectric loss and preparation method thereof

    CN113563075A

  • Potassium-sodium niobate-based leadless piezoelectric ceramic as well as preparation method and application thereof

    CN114262228A